2013
DOI: 10.1007/s13762-012-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of styrene removal in air by positive and negative DC corona discharges

Abstract: This communication discusses styrene removal in air by positive and negative DC corona discharges. Experiments were performed with a wire-plate reactor and under a gas flow rate of 305 m 3 /h. In terms of averaged applied voltage and corona current, it is observed that the maximum negative corona current is always at least two times larger than the positive one at the same voltage level. At the same corona discharge energy density, however, the positive corona discharge produces around 2-6 times more ozone in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
3
3
0
1
Order By: Relevance
“…However, the ozone concentration formed in the positive DC is higher than that in the negative DC under the same applied voltage. Similar results were presented by Zhang et al and Hegeler et al, who found that the positive corona discharge produces around 2–6 times more ozone in comparison with the negative corona. Many researches showed that a brilliant and uniform streamer corona occurs in the reactor of positive DC, which, the glow corona was observed for negative DC. , Since the electric field strength in the discharge gap is sufficient to generate streamers, it should be also adequate for the electrons to gain the energy required for dissociation of O 2 molecules to synthesis ozone molecules. …”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the ozone concentration formed in the positive DC is higher than that in the negative DC under the same applied voltage. Similar results were presented by Zhang et al and Hegeler et al, who found that the positive corona discharge produces around 2–6 times more ozone in comparison with the negative corona. Many researches showed that a brilliant and uniform streamer corona occurs in the reactor of positive DC, which, the glow corona was observed for negative DC. , Since the electric field strength in the discharge gap is sufficient to generate streamers, it should be also adequate for the electrons to gain the energy required for dissociation of O 2 molecules to synthesis ozone molecules. …”
Section: Results and Discussionsupporting
confidence: 90%
“…However, the ozone concentration formed in the positive DC is higher than that in the negative DC under the same applied voltage. Similar results were presented by Zhang et al 21 and Hegeler et al, 22 who found that the positive corona discharge produces around 2−6 times more ozone in comparison with the negative corona. Many researches showed that a brilliant and uniform streamer corona occurs in the reactor of positive DC, which, the glow corona was observed for negative DC.…”
Section: Effects Of Thorn Numbersupporting
confidence: 88%
“…In real life, most industrial emissions contain VOC mixtures. However, the studied pollutants have often been single component VOCs [ 17 , 18 , 19 , 20 ]. Mok et al studied the abatement of trichloromethane using nonthermal plasma reactors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mok et al studied the abatement of trichloromethane using nonthermal plasma reactors [ 21 ]. Zhang et al compared styrene removal in air by positive and negative DC corona discharges, and reported that positive corona processing was more effective [ 20 ]. In the present study, a recalcitrant VOC mixture, styrene and o -xylene, was employed as the target contamination with a cylindrical DBD plasma configuration at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…3) увеличены и можно сделать важный вывод о том, что процессы в коронном разряде различной полярности протекают по сходному механизму, но эффективность использования энергии разряда в данном случае для отрицательной короны выше, чем в случае положительной. В литературе опи-сано различное влияние полярности короны на процесс, например [20,21]. В целом процессы в значительной части определяются объемом разрядного промежутка с увеличенным градиентом поля, где создаются электроны с энергией, достаточной для диссоциации компонентов газовой среды.…”
Section: обсуждение результатовunclassified